Comparative study of in vitro effects of different nanoparticles at non-cytotoxic concentration on the adherens junction of human vascular endothelial cells - Wen T (Dove Medical Press, 2019)
Tao Wen,1,* Aiyun Yang,1,* Lingyu Piao,2 Suisui Hao,1 Lifan Du,1 Jie Meng,1 Jian Liu,1 Haiyan Xu11Institute of Basic Medical Sciences, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing 100005, People’s Republic of China; 2CAS Center for Excellence in Nanoscience, CAS Key Laboratory of Standardization and Measurement for Nanotechnology, National Center for Nanoscience and Technology, Beijing, 100190, People’s Republic of China*These authors contributed equally to this work Background: Effects of different nanoparticles (NPs) exposure at acutely non-cytotoxic concentrations are particularly worthy to figure out, compare, and elucidate. Objective: To investigate and compare the effect of a small library of NPs at non-cytotoxic concentration on the adherens junction of human umbilical vein endothelial cells (HUVECs), obtaining new insights of NPs safety evaluation. Materials and methods: The HUVECs layer was exposed to NPs including gold (Au), platinum (Pt), silica (SiO2), titanium dioxide (TiO2), ferric oxide (Fe2O3), oxidized multi-walled carbon nanotubes, with different surface chemistry and size distribution. Cellular uptake of NPs was observed by transmission electron microscopy. and the cytotoxicity was determined by Cell Counting Kit-8 assay. The NP-induced variation of intracellular reactive oxygen species (ROS) and catalase (CAT) activity was measured using the probe of 2ʹ7’-dichlorodihydr fluorescein diacetate and a CAT analysis kit, respectively. The level of VE-cadherin of HUVECs was analyzed by Western blot, and the loss of adherens junction was observed with laser confocal microscopy. Results: The acutely non-cytotoxic concentrations of different NPs were determined and applied to HUVECs. The NPs increased the level of intracellular ROS and the activity of CAT to different degrees, depending on the characteristics. At the same time, the HUVECs lost their adherens junction protein VE-cadherin and gaps were formed between the cells. The NP-induced oxidative stress and gap formation could be rescued by the supplementary N-acetylcysteine in the incubation. Conclusion: The increase of intracellular ROS and CAT activity was one common effect of NPs, even at the non-cytotoxic concentration, and the degree was dependent on the composition, surface chemistry, and size distribution of the NP. The effect led to the gap formation between the cells, while could be rescued by the antioxidant. Therefore, the variation of adherens junction between endothelial cells was suggested to evaluate for NPs when used as therapeutics and diagnostics. Keywords: reactive oxygen species (ROS), catalase, HUVEC, VE-cadherin